Key Success Factors in Wild Boars Football Academy Rescue Mission - Suebvises, Ploy (NIDA Case Research Journal, 2020)
Boys and assistant coach of Wild Boars Football Academy, all together 13 people, went exploring in Thamluang Khunnam Nangnon cave and remained stranded inside as rainwater impeded them to escape. Rescue mission went difficultly because of obstacles and limitations which were heavy rain that flooded the cave complex; turbidity muddy water; complexity of the cave’s internal structure; experience and knowledge in cave diving; period that victims can still survive; drop of oxygen levels inside the cave; health and other side issues as well as upcoming monsoon season. This rescue mission gripped the world's attention and support. It was an accomplished and world-famous rescue mission of 2018. “Tham Luang Rescue Operation Center”, hub of the rescue operation, obtained domestic and international cooperation from government agencies, private sectors as well as civil society in searching, planning, preparing and carrying out the rescue mission. Wild Boars Football Academy Rescue Mission is an interesting lesson learned in organization studies. Key success factors in this mission can be explained through the theory of Adhocracy organization, Crisis management, and Leadership. These key success factors can be applied when emergencies or crises occur. Keywords: Adhocracy, Leadership, Crisis management